The Intertexts of German Culture in Jurgis Kunčinas’s Poetry - Jasaitytė, Jūratė (Colloquia, 2025)
This article examines motifs and intertexts from German culture and literature in the poems of Lithuanian writer and translator Jurgis Kunčinas. It argues that Kunčinas’s personal and professional connections with the German language and culture determined their distinctive reflection in his work. The article demonstrates, through analytical process, alternative interpretations of Kunčinas’s poems that are seemingly established and detached from certain initial assessments. The study addresses three aspects: the preservation of memory, its reactivation, and the search for self-identification across generations, as well as the influence of German writers and artists on Kunčinas’s poetry.